Exploring of a small-scale tourism product under economic instability: The case of a Greek rural border area - Fotios Chatzitheodoridis; Achilleas Kontogeorgos (Economies, 2020)
The Regional Unit of Kastoria is a rural area in Northwestern Greece, located on the borderline with Albania. Kastoria city, the capital and the largest city of the Kastoria Regional Unit, is known for the production of high-quality fur products. The fur industry has faced a marked crisis from the 1980s onwards, which has contributed to pushing the local economy towards the development of tourism. However, the tourism industry, developed during the last 20 years, has an undefined character. Specifically, tourism is characterized as small-scaled owing to the limited number of mainly domestic tourists, who, in combination with the economic crisis of the last decade, slowed down the initial accelerated trend. The purpose of this paper is to capture the opinions and attitude of Kastoria visitors towards tourism, as well as to illustrate the changes as a consequence of the economic crisis. In this context, a survey was carried out in two periods (in 2008 at the beginning of economic crisis and in 2017 at the end of this crisis) using a structured questionnaire and with a sample of 232 visitors in total. Our findings are highlighted in an effort for policy makers and marketing planners to formulate appropriate marketing strategies and to reconstruct and promote the local touristic product and attract visitors in these border areas.
Keywords: L83; O20; R12; 330; tourism product; rural tourism; economic crisis; border areas; Greece